PENGIKATAN KARBON DIOKSIDA DENGAN MIKROALGA ( Chlorella vulgaris, Chlamydomonas sp., Spirullina sp. ) DALAM UPAYA UNTUK MENINGKATKAN KEMURNIAN BIOGAS - Okryreza Abdurrachman; Meitiandari Mutiara; Luqman Buchori (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2013)
Biogas is gas which the main contents are 55-75% methane and 25-45% carbon dioxide. Removing CO2 content in biogas will improving biogas’s quality itself, so that the calorific value on biogas will be higher. One way to removing CO2is with utilize microalgae’s ability to absorb CO2in photosynthesis phenomena. Purposes of this research are to measure the optimal amount of CO2 absorbed by microalgae and determine the type of microalgae is the best at absorbing CO2. This research designed with variety types of microalgae such as Chlorella vulgaris, Chlamydomonas sp., and Spirulina sp. and variety gas flow rate variabels are 20, 60, 100, 150, 200, 300 mL / min. From analysis results, at gas flow rate 20 mL / min each microalgae can absorb CO2optimally. Spirullina sp. has the highest percentage of absorbed CO2 among Chlorella vulgaris and Chlamydomonas sp., which is by 8,91%. This study also showed that Spirullina sp. has 0,136 g/L biomass enhancement, and that is the highest biomass enhancement among Chlorella sp. and Chlamydomonas sp., which only has 0,136 g/L and 0,130 g/L biomass enhancement.